2003
DOI: 10.1016/j.curtheres.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of levofloxacin in the context of other contemporary fluoroquinolones: a review

Abstract: Background: In recent years, fluoroquinolone research has focused on achieving several goals, including (1) enhanced potency against gram-positive cocci, notably Streptococcus pneumoniae, and anaerobes, while (2) maintaining potency against gram-negative pathogens, (3) optimizing pharmacokinetics and pharmacodynamics (PK/PD), and (4) minimizing potential adverse drug reactions through recognition and avoidance of structural configurations that have characterized earlier, reactive compounds.Objective: This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…In line with our findings, Ball P reported that the most common predisposing factor for quinolones-induced ADRs is advanced age (risk increases with age after 60 years) (Ball, 2003). In this regard, one can suppose that the altered renal function, which is relatively common in older people, may affect the excretion of quinolones leading to higher risk in the occurrence of musculoskeletal, neurological, and psychiatric ADRs.…”
Section: Agesupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, Ball P reported that the most common predisposing factor for quinolones-induced ADRs is advanced age (risk increases with age after 60 years) (Ball, 2003). In this regard, one can suppose that the altered renal function, which is relatively common in older people, may affect the excretion of quinolones leading to higher risk in the occurrence of musculoskeletal, neurological, and psychiatric ADRs.…”
Section: Agesupporting
confidence: 90%
“…Although the exact pathologic mechanisms underlying quinolone-induced musculoskeletal ADRs are still poorly understood, it was suggested that such antibiotics might alter tendon fibroblast metabolism, leading to collagen damage (Shakibaei et al, 2000;Williams et al, 2000). These ADRs seem to be rare, affecting <1 in 5,000 patients receiving quinolones with an overall incidence of three cases per 1,000 patient years, even though some quinolones, such as pefloxacin, show an increased risk (Ball, 2003). On the other hand, the occurrence of both neurological and psychiatric ADRs may have several underlying factors, including the higher penetration of quinolones across the blood-brain barrier (such as pefloxacin that shows convulsant activity) (Kushner et al, 2001;Sarro and Sarro, 2012) and the interaction with the activity of neurotransmitters, including the displacement of GABA from its receptors GABA-A or the direct effect on excitatory brain pathways on N-methyl-D-aspartate and a-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid receptors (Mehlhorn and Brown, 2007;Rubio-Nazabal et al, 2013).…”
Section: Soc -Reported Adverse Eventsmentioning
confidence: 99%
“…This shows that the principal use of fluoroquinolones was for the treatment of urinary tract infections (36% of con- sumption; volume of 0.95 DIDs) and lower respiratory tract infections (26% of consumption; volume of 0.70 DIDs). This suggests that fluoroquinolones were used primarily for those indications where they have been shown to yield clinical benefit (1,2). Fluoroquinolones were used marginally for the management of upper respiratory tract infections, with a share of consumption of 2% (volume of 0.21 DIDs).…”
mentioning
confidence: 99%
“…3 shows that the principal use of fluoroquinolones was in the treatment of urinary tract infections (35% of consumption; volume of 1.06 DID) and lower respiratory tract infections (24% of consumption; volume of 0.71 DID). Management of upper respiratory tract infections with fluoroquinolones amounted to 9% of consumption (volume [12,13].…”
Section: Breakdown Of Consumption By Type Of Infectionmentioning
confidence: 99%